THE EFFECT OF MUSIC THERAPY ON PEAK EXPIRATORY FLOW, ANXIETY, AND DEPRESSION IN COPD PATIENTS - Rudi Hariyono; Rizky Meuthia Pratiwi; Siti Kotijah (Indonesian Journal for Health Sciences, 2021)
Introduction: Biopsychological factors of anxiety in patients with Chronic Obstructive Pulmonary Disease (COPD) will cause symptoms of increased respiration rate and prolonged expiration duration. Meanwhile, depression in COPD patients will increase the damage to lung functional capacity. This study aims to determine the difference in the impact of music therapy on increasing the value of peak expiratory flow rate, anxiety, and depression in the treatment group and the control group. Methods: Quasi-experimental one group pre-test-post test was conducted on 46 COPD patients in RSUD  Prof. Dr. Soekandar  Mojosari and RSUD  Basoeni Mojokerto with simple random sampling technique. This research was conducted by providing music therapy intervention in the treatment group. The statistical test used was the Independent t-test to determine the difference in peak expiratory flow values in the two groups, while the Mann-Whitney U test was used to determine the difference between anxiety and depression in the two groups. Results: There were differences in the intervention group who received music therapy with the control group with p-value = 0.005 (p 0.05), and the difference between anxiety (Z = -3.813) and depression (Z = -3.868) values with an asymp sign value. = 0,000. Conclusion: There are differences in PEF values, anxiety, and depression between the treatment group and the control group, where this therapy affects the PEF value, anxiety, and depression.